A mixed-methods approach to conducting Internal Revenue Service-compliant community health needs assessments: a case example for nonprofit hospital leaders - Oglesby WH; Slenkovich K (Dove Medical Press, 2014)
Willie H Oglesby, Ken Slenkovich Department of Health Policy and Management, College of Public Health, Kent State University, Kent, OH, USA Background: The Patient Protection and Affordable Care Act created new requirements for nonprofit hospitals to conduct a Community Health Needs Assessment (CHNA) at least once every 3 years, with a significant tax penalty for noncompliance. While some resources exist to help nonprofit hospital leaders conduct various aspects of a CHNA, few reflect the new Internal Revenue Service requirements. Methods: Many different models of CHNAs have emerged over the years. Although each has its unique features, the essential elements of a CHNA include engaging stakeholders, defining the community, gathering sufficient representative data, prioritizing information, and reporting results. In this paper, we expand upon this basic approach by offering a practical step-by-step guide to conducting CHNAs that meets new Internal Revenue Service regulations. Results: We developed and tested this methodology in partnership with several nonprofit hospital systems in Northeast Ohio, USA. In this paper, we discuss our use of the methodology and identify recommendations for other nonprofit hospital leaders. Conclusion: The methodology presented in this paper is a cost-effective approach to satisfying new CHNA requirements and nonprofit hospital leaders should consider using it or modifying it to fit their unique needs. Keywords: Affordable Care Act, CHNA, community benefit, community hospital